Feasibility and effects of home-based smartphone-delivered automated feedback training for gait in people with Parkinson's disease: A pilot randomized controlled trial. (January 2016) - Ginis, Pieter; Nieuwboer, Alice; Dorfman, Moran; Ferrari, Alberto; Gazit, Eran; Canning, Colleen G.; Rocchi, Laura; Chiari, Lorenzo; Hausdorff, Jeffrey M.; Mirelman, Anat
Abstract: Background: Inertial measurement units combined with a smartphone application (CuPiD-system) were developed to provide people with Parkinson's disease (PD) real-time feedback on gait performance. This study investigated the CuPiD-system's feasibility and effectiveness compared with conventional gait training when applied in the home environment. Methods: Forty persons with PD undertook gait training for 30 min, three times per week for six weeks. Participants were randomly assigned to i) CuPiD, in which a smartphone application offered positive and corrective feedback on gait, or ii) an active control, in which personalized gait advice was provided. Gait, balance, endurance and quality of life were assessed before and after training and at four weeks follow-up using standardized tests. Results: Both groups improved significantly on the primary outcomes (single and dual task gait speed) at post-test and follow-up. The CuPiD group improved significantly more on balance (MiniBESTest) at post-test (from 24.8 to 26.1, SD∼5) and maintained quality of life (SF-36 physical health) at follow-up whereas the control group deteriorated (from 50.4 to 48.3, SD∼16). No other statistically significant differences were found between the two groups. The CuPiD system was well-tolerated and participants found the tool user-friendly. Conclusion: CuPiD was feasible, well-accepted and seemed to be an effective approach to promote gait training, as participants improved equally to controls. This benefit may be ascribed to the real-time feedback, stimulating corrective actions and promoting self-efficacy to achieve optimal performance. Further optimization of the system and adequately-powered studies are warranted to corroborate these findings and determine cost-effectiveness. Highlights: CuPiD's Smartphone-delivered gait training system is feasible for at-home use in PD. Gait improvements were found after 6 weeks of training and retained 4 weeks later. The CuPiD-system was equally effective for gait training as standard physiotherapy. PD people's balance improved more after training with than without the CuPiD-system.